Pre-service Teachers’ Motivations to Participate in the Near-Peer Mentoring Program - Busra Karga; Ilkem Ozdinc; Dilara Kara-zorluoglu; Gaye Ceyhan (Sakarya University Journal of Education)
Recent research indicates that college students experienced increased stress and academic anxiety during the Covid-19 era. Near-peer mentoring is a program that pairs students in different grade levels with the goal of enhancing their academic, emotional, and social development. This study uses the Expectancy-Value Theory to examine the motivation of pre-service science teachers to participate as mentors in the near-peer mentoring program, and the costs they attach to participating in the program. The qualitative research was conducted with a total of twelve pre-service science teachers. Data were collected through individual interviews during the spring semester of 2021. Results revealed that participants found the program useful, benefited from this program in terms of social/emotional support and academic career, and stated that it would be more beneficial if the content of the program were improved. The participants’ motivation to participate in the near-peer mentoring program were categorized into seven, from the most beneficial to the least, as follows: (1) developing learning strategies, (2) career planning, (3) access to university services, (4) communication, (5) sense of belonging, (6) academic development, and (7) support in registration and course selection. This research carries notable importance as it can strengthen the sense of community among pre-service teachers. This study is likely to provide an opportunity for the design of near-peer mentoring programs in universities and the development of content in accordance with the findings. Furthermore, the insights derived from this study can be crucial in designing and implementing effective near-peer mentoring programs at tertiary education levels, promising mutual benefits for both the mentor and the mentees.